Metal nanostructures for surface-enhanced Raman scattering and its coupling with ZNO - Liu, Mo-Nan (2013)
This thesis includes research work of two main parts. The first part is focused on metal plasmonic nanostructures for surfaced enhanced Raman spectroscopy and molecule probing. Their properties for plasmonic field concentration towards inorganic molecule probing have been well characterized by SERS measurements. The second part is a comprehensive study using both macroscopic PL and microscopic CL on the greatly-enhanced near bandgap emission of ZnO nanorods (NRs) based on metal/Al2O3 capping. The extraordinary radiation engineering featured with ultrahigh emission enhancement has been ascribed primarily, among other possibilities, to plasmonic coupling with ZnO excitons.